Synergistic effect of physico-chemical properties and reaction temperature on the gasification of coal-waste activated carbon-slurry coke for H2 production. (1st November 2022) - Wang, Jianbin; Liu, Jianzhong; Zhang, Lei; Dai, Shiliang; Li, Anan; Chen, Jian
Graphical abstract: Highlights: Waste activated carbon was recycled for H2 production. Synergistic effects of coke properties and reaction temperature were investigated. Coke samples pyrolyzed at 400 °C and 500 °C exhibited higher gasification reactivity. Increasing the gasification temperature is beneficial to H2 production to an extent. Coke pyrolyzed at 500 °C showed the highest degree of disorder and carbon activity. Abstract: The gasification of coal water slurry represents a promising way to recycle waste activated carbon. Here, the synergistic effects of physico-chemical properties and reaction temperature on the gasification of coal-waste activated carbon-slurry coke for H2 production were investigated. The results showed that the coke samples pyrolyzed at 600 °C and 700 °C exhibited larger crystallite sizes and lower gasification reactivity, while those pyrolyzed at 400 °C and 500 °C showed higher gasification reactivity. In addition, the coke sample pyrolyzed at 500 °C achieved the highest H2 yield of 3051 mL, at a gasification temperature of 1200 °C. Overall, increasing the gasification temperature is beneficial to H2 production to an extent, but that too high a temperature may also inhibit the reaction. The alkali and alkaline earth metal elements present in the coke samples pyrolyzed at 400 °C and 500 °C showed stronger catalytic activity towards gasification, with the sample pyrolyzed at 500 °C exhibiting the highest degree of disorder and carbon activity, as its disordered carbon lattice increases the defects in the microcrystalline structure, which facilitates contact between carbon and steam molecules.